Systematic Review : Dampak Psikoligis Kesehatan Terhadap Korban Kekerasan Seksusal di Indonesia - Putri, Felysitas Gayatri; Prajnawita, Disny (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Sexual violence is a form of human rights violation that has serious impacts on the physical, mental, and social conditions of victims. In Indonesia, the rate of sexual violence continues to show an alarming trend. According to Komnas Perempuan (National Commission on Violence Against Women) data in 2023, there were 457,895 reported cases of violence against women, with approximately 30% involving sexual violence. This systematic review aims to systematically examine the psychological health impacts on victims of sexual violence in Indonesia based on empirical studies from the last three years. Methods: This study used a systematic review design with an article search strategy guided by the PICOS framework. The articles were sourced from the Google Scholar database, and 5 articles that met the inclusion criteria were selected. Keywords used in the search included “sexual violence,” “psychological impact,” “victims,” “mental health,” AND “Indonesia” OR “Indonesia.” Articles were then screened using the PRISMA-P method. Results and Analysis: Based on the reviewed literature, psychological impacts on victims of sexual violence in Indonesia include PTSD, anxiety, and depression. Social and environmental support significantly influence the victims’ recovery process. Moreover, stigma from society and families remains the biggest barrier for victims to access adequate psychological assistance.